The Contribution of Total Quality Management Dimensions to Achieving a Sustainable Competitive Advantage: An Empirical Study Based on the Perspectives of Employees at Al-Basha Pure Water Factory - Jasim, Reem I. (PROSPECTIVE RESEARCHES, 2026)
This research aims to examine the role of Total Quality Management (TQM) in enhancing sustainable competitive advantage at Al-Basha Pure Water Plant. TQM is an important strategy that contributes to improving organizational performance and achieving excellence in institutions, enhancing their ability to compete in the labor market. The research examines the role of TQM dimensions within the plant and how these dimensions influence enhancing sustainable competitive advantage. The research also reviews the factors that help the plant maintain a sustainable competitive advantage through continuous innovation, continuous process improvement, and a focus on customer satisfaction. The research relied on analyzing quantitative and qualitative data by distributing questionnaires to the research sample, in addition to studying the relevant literature. The research concluded that the effective implementation of TQM at Al-Basha Pure Water Plant has significantly contributed to improving product quality and increasing operational efficiency, which has helped the plant strengthen its competitive position in the market and achieve sustainability in the face of external challenges.